Atypical Presentation of Non-ossifying Fibroma - Datta, NK; Das, KP; Ahamed, SU (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):434-7 The abstract of this article is available on the PubMed website